Ryoko Sekiguchi: Exile Between Simultaneity and Superimposition - Marino, Valeria (Oltreoceano - Rivista sulle migrazioni, 2024)
In an interview, Ryoko Sekiguchi remarked about her experience of exile: "exiled people always live two seasons simultaneously" (2021). This means, for example, that in winter she can live with the sky of Tokyo, Beirut or Granada, while being in Paris. This imaginative ubiquity of presence is not only at the center of her condition as a foreigner in France, but also at the heart of her poetic work, involving space-times characterized by a principle of simultaneity and by the constant attempt to superimpose several texts or several voices on the same sensitive surface. In this study, we analyze the role played by simultaneity and superimposition as poetic and heuristic tools in the poet's work. Among the works that make up his vast corpus, we have chosen to focus on Heliotropes. This book seems particularly significant to us, since it bases the simultaneity of all its constituent elements on the superposition between the poetic world and the world of plants. After briefly presenting the text, we explore the superposition between textual forms and plant forms in order to identify the principles of spatialization that allow Sekiguchi to neutralize time: we first look at the isomorphy between metric block and botanical block, because the measure chosen by the author is based on a principle of crystallization that leaves no room for random proliferation and reminds us, on the one hand, the geometric principles governing the formation of the regular and symmetrical structures of plants, and on the other, the desire for order that allows nature to be landscaped as a garden. Then, we examine the analogy between the forms of textual grafting and the so-called plant grafts. We thus wish to reconstruct the movements and space-times of this writing of exile which is configured as the simultaneous listening of multiple sounds.